The global wellposedness of the 3D heat-conducting viscous incompressible fluids with bounded density. (April 2015) - Zhang, Xu; Tan, Zhong
Abstract: We consider the global wellposedness of the inhomogeneous incompressible heat-conducting viscous fluids in three dimension space. We generalize the result of Fujita & Kato for Navier–Stokes to the heat-conducting inhomogeneous incompressible viscous fluids. The key point is that we get the global wellposedness under the assumption that the initial density has positive lower and upper bound and the initial temperature can be arbitrarily large.